The Creation of Church Administrative Tribunals At the Diocesan Level: A Permanent Desideratum in the History of Codification to CIC/1983 - Pulte, Matthias (Revision of the Codes, 2018)
The legal protection against administrative acts of the hierarchy is a topic of permanent discussion in European Canon Law since the promulgation of the 1983 Code. However, the law making initiatives in between 1968 and 1983 (finally realized with some basic norms in the "Lex Ecclesiae Fundamentalis") have not been integrated in the present legislation. It is disappointing that the universal legislator missed the opportunity to ensure legal protection, guaranteed in can. 221 in all fields of Church life. The basic administrative jurisdiction by the "Segnatura Apostolica" does not fulfil the necessary requirements. The tension between the fundamental rights of religious individuals and the law is still prevalent. This article purports to strengthen the arguments supporting the need to erect an administrative jurisdiction in the level of particular Churches. I argue there is no need for a uniform worldwide structure, but for a consistent two-staged juridical system on the level of each bishops' conference. To ensure legal protection in the legal affairs of the Church, the establishment of administrative tribunals would promote the legally guaranteed basic rights of all faithful and strengthen the credibility of the Church in the interior and exterior fields.